2009
DOI: 10.5194/acpd-9-2165-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen cyanide in the upper troposphere: GEM-AQ simulation and comparison with ACE-FTS observations

Abstract: Abstract. We investigate the spatial and temporal distribution of hydrogen cyanide (HCN) in the upper troposphere through numerical simulations and comparison with observations from a space-based instrument. To perform the simulations, we used the Global Environmental Multiscale Air Quality model (GEM-AQ), which is based on the three-dimensional global multiscale model developed by the Meteorological Service of Canada for operational weather forecasting. The model was run for the period 2004–2006 on a 1.5°×1.5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Li et al: Observed variability of HCN in the troposphere and lower stratosphere main sink. Recently Lupu et al (2009) reproduced similar seasonal variations of the HCN tropospheric column using the GEM-AQ tropospheric global 3-D model.…”
Section: Introductionmentioning
confidence: 91%
“…Li et al: Observed variability of HCN in the troposphere and lower stratosphere main sink. Recently Lupu et al (2009) reproduced similar seasonal variations of the HCN tropospheric column using the GEM-AQ tropospheric global 3-D model.…”
Section: Introductionmentioning
confidence: 91%
“…Global HCN emission inventories are subject to large uncertainties. However, there are no indications of substantial interannual variability of HCN emissions outside of Indonesia [Schultz et al, 2008;Lupu et al, 2009], so they are neglected here.…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%
“…Over land the uptake of HCN is neglected. Lupu et al [2009] performed a model study of HCN in the upper troposphere and were able to reproduce the observed variability of the volume mixing ratio of HCN in the troposphere and a residence time of ≈5 month.…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%
“…Both the "HCN-plumes" and "C 2 H 6 -plumes" agree fairly well in location and in magnitude of the mixing-ratios. A more detailed comparison can be made with the ACE HCN data in Lupu et al (2009) Li et al, 2003). These authors report mean values of 260 pptv at 9 km and 240 pptv at 11 km altitude over the Northern Pacific (10 • N-40 • N), whereas the respective MIPAS values are 220-240 pptv (Fig.…”
Section: Comparison With Other Space- Airborne and Ground-based Measmentioning
confidence: 99%
“…The lifetime of stratospheric HCN, where the main sink is reaction with OH, is still assumed to be several years. Recent spaceborne observations of HCN are performed by the Atmospheric Chemistry Instrument (ACE) on SCISAT (Rinsland et al, 2005;Lupu et al, 2009) and by the Microwave Limb Sounder (MLS) on EOS (Pumphrey et al, 2006). C 2 H 6 is the most important non-methane hydrocarbon (NMHC) in the troposphere (Singh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%